The relationship between the level of satisfaction on the growth of Instagramable Place and Motivation of the Users in increasing Income - Cynthia Setiawan; Lamtiur Hasianna Tampubolon (Universitas Diponegoro, 2020)
Instagram in Indonesia is used as a Marketing Strategy. Along with the development of the use of Instagram, gave rise to the trend of new lifestyles and habits that have an impact on the improvement of the appearance of Instagramable places. One of the most Instagramable which became the goal of the millennial generation is the island of Bali. The island is a tourist destination that is a complete, integrated and has many tourist attractions Instagramable. The purpose of this research is to study the relationship between the level of satisfaction on the growth of Instagramable places and motivation of the users in increasing income. The type of research used in this study is a research associate with the use of quantitative methods and data collection techniques with the dissemination of the questionnaire to the 130 respondents. The research concludes there is a positive relationship with the level of medium strength between the satisfaction on the growth of instagramable place and the motivation of users in increasing their income with a score of 0.486 using the calculation of the correlation test manually.